Phenotypic and genotypic characterization of lactic acid bacteria isolated from cow, ewe and goat dairy artisanal farmhouses - Stella M. Reginensi (Brazilian Journal of Microbiology, 2013)
Lactic acid bacteria collected from artisanal farmhouses were characterized using a polyphasic approach. Phenotypic methods including biochemical assays, ribosomal DNA restriction analysis and 16S rDNA sequence analysis were performed. This approach provides accuracy for identification, and helps to avoid the loss of natural biodiversity including potentially valuable strains.